2018
DOI: 10.1101/280768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aneuploidy promotes intestinal dysplasia in Drosophila

Abstract: Aneuploidy is associated with different human diseases, particularly cancer, but how different cell types within tissues respond to aneuploidy is not fully understood. In some studies, aneuploidy has been shown to have a deleterious effect and lead to cell death, however it has also been shown to be a causal event of tumorigenesis in other contexts.Here, we show that Drosophila intestinal stem cells have a particular tolerance to aneuploidy and do not activate apoptosis in response to chromosome misegregation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Our BubR1 kinase-dead mutants seemed to be diploid according to the assessments done in embryos and neuroblasts (Figures 1 and S1); however, they had reduced numbers of ISCs and EE cells, suggesting that this reduction was a reflection of the attenuated insulin signaling in these mutants. The finding also implies that the varying numbers of ISCs seen in the previous studies (Gogendeau et al, 2015;Resende et al, 2018) could be a joint consequence of increased aneuploidy and compromised insulin signaling, which we think is also the reason for the complex phenotypes observed in our BubR1 AAN mutant.…”
Section: Loss Of Bubr1 Kinase Activity Compromises the Homeostasis Of Stem Cellssupporting
confidence: 53%
See 2 more Smart Citations
“…Our BubR1 kinase-dead mutants seemed to be diploid according to the assessments done in embryos and neuroblasts (Figures 1 and S1); however, they had reduced numbers of ISCs and EE cells, suggesting that this reduction was a reflection of the attenuated insulin signaling in these mutants. The finding also implies that the varying numbers of ISCs seen in the previous studies (Gogendeau et al, 2015;Resende et al, 2018) could be a joint consequence of increased aneuploidy and compromised insulin signaling, which we think is also the reason for the complex phenotypes observed in our BubR1 AAN mutant.…”
Section: Loss Of Bubr1 Kinase Activity Compromises the Homeostasis Of Stem Cellssupporting
confidence: 53%
“…How ISCs are affected by mutations in BubR1 is not clear and may be complex. Previous studies in SAC-deficient flies suggested that aneuploidy influences ISC numbers, but the results were contradictory (Gogendeau et al, 2015;Resende et al, 2018). Although the depletion of different SAC components increased the aneuploidy rate, the knockdown of Bub3 reduced the number of ISCs, whereas depletion of Mad2, Mps1, or BubR1 caused the overproliferation of ISCs.…”
Section: Loss Of Bubr1 Kinase Activity Compromises the Homeostasis Of Stem Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…The impact of aneuploidy on differentiation has been investigated in both embryonic and adult stem cells in a variety of organisms. 40,41,[47][48][49] Our data suggest that aneuploidy impairs differentiation of human colon stem cells, which have been demonstrated to be the cell of origin in colorectal cancer. 50 Our finding is consistent with the observation that aneuploidy resulted in significant expansion of the proliferative zone in intestinal crypts in a mouse model of chromosomal instability.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies, using different experimental models, showed that the fate of aneuploid cells, especially p53 activation and cell cycle arrest, is varied and may be dependent on cellular and physiological contexts. [38][39][40][41][42] Here, we investigated the effect of aneuploidy within the normal colon epithelium using patient-derived human colonoids. Using high-depth, full-length single cell RNA sequencing, biochemical assays, and live cell imaging approaches, our data suggest that the degree of aneuploidy plays a significant role in determining how cells respond.…”
Section: Discussionmentioning
confidence: 99%